Epidemiology, diagnostic and management of abdominal trauma in two hospitals in the city of Douala, Cameroon - Engbang, Jean Paul; Chasim, Christian Beughuem; Fouda, Bekolo; Motah, Mathieu; Moukoury, Thomas Jim Kevin; Ngowe, Marcelin Ngowe (International Surgery Journal, 2021)
Background: Abdominal trauma remains quite common in the general world and in developing countries in particular. The accidents in the public roads are the main cause and also the assumption of responsibility which remains questionable. Methods: It was a descriptive longitudinal study, carried out from 31 December 2018 to 19 April 2019, in Laquintinie and General hospital in Douala, Cameroon. Patients admitted for abdominal trauma and treatment in the emergency department, operating theater and visceral surgery were included in the study. Results: We found 21.2% (43 cases) of abdominal trauma in our series. Abdominal trauma mainly affected adults between 20 and 39 years old (27 cases, 63%) in our series. The male sex was most affected, with sex ration of 3.3. Road accidents occupy the first place with 34.9% (15 cases). Wounds in our series represented 27.9% (12 cases) and contusions 72.1% (31 cases). In fact, Abdomen without preparation was performed in 7.0% (3 cases) of cases, abdominal ultrasound in 48.8% (21 cases) and abdominal CT scan in 25.6% of patients (11 cases). The organs affected in order were the spleen, small intestine, colon, stomach and liver. We recorded postoperative complications with a morbidity of 11.6% with a single case of parietal suppuration and no death. Conclusions: In our context abdominal trauma remains quite frequent and concern particularly young people. The prevention of accidents on the public highway and the improvement of diagnostic and surveillance methods are the key for reducing this phenomenon leading to good management.